Effects of elevated temperature on estrogenic induction of Vtg and Zp gene expression in salmon - Anderson, K; King, H R; Pankhurst, N W; Ruff, N; Pankhurst, P M; Elizur, A (2012)
Fertility and embryo survival rates are often low in eggs from Tasmanian Atlantic salmon exposed to high summer temperatures, partly due to a reduction in plasma 17β-estradiol (E2) levels, and a subsequent decrease in the transcription levels of vitellogenin (Vtg) and zona pellucida (Zp) genes. We used juvenile Atlantic salmon in a pilot study to assess whether hepatic tissue remains responsive to stimulation by E2 at two temperatures that are relevant to the salmon industry. E2-administration stimulated Vtg and estrogen receptor alpha transcription and increased the levels of plasma Vtg at 14 °C and 22 °C. However, hepatic Zp B and C transcription was significantly lower in E2-treated fish at 22°C relative to 14°C, indicating that these genes display traits of thermal inhibition. Trialling E2-therapy in adult fish resulted in a marked increase in egg size at 22 °C due to enhanced Vtg production. However, Zp transcription, egg fertility and embryo survival were unaffected by E2-treatment at high temperature. This suggests that unique (non-E2-dependent) factors regulating the expression of Zps but not Vtg are temperature-sensitive, and thermal inhibition of endocrine process is difficult to overcome using hormonal therapies.